Comparative analysis of calculation possibilities of MACCS and RODOS computer codes for tasks of emergency response and analysis of radiation consequences of severe accidents at NPPs - Bogorad, V.; Lytvynska, T.; Bielov, Ia. (Ядерна та радіаційна безпека, 2016)
The paper provides a brief description of the Real-time On-line Decision Support system (RODOS) and MELCOR Accident Consequence Code System (MACCS) computer code and evaluates the application of these codes for assessment of radiation impact on the public and environment in case of a severe accident at NPPs in real time mode. The results of calculations performed using RODOS, WinMACCS and HotSpot codes are compared. In the framework of research, the chosen comparative criteria were assessed: total effective dose, thyroid equivalent dose, skin equivalent dose, I-131 and Cs-137 ground concentration at different distances up to 50 kilometers from the point of release. Наведено стислий опис Європейської системи прогнозу радіаційних наслідків у режимі реального часу RODOS та розрахункового коду MELCOR Accident Consequence Code System (MACCS), розглянуто можливість застосування цих кодів для оцінки впливу радіаційного опромінення на населення та навколишнє середовище в умовах тяжкої аварії на АЕС у режимі реального часу. Виконано порівняльний аналіз результатів розрахунків, проведених з використанням кодів RODOS, WinMACCS та HotSpot. У рамках дослідження для розгляду обрано такі критерії: ефективна доза опромінення, еквівалентні дози опромінення щитоподібної залози та шкіри, поверхневі концентрації радіонуклідів I-131 та Cs-137 на відстанях до 50 км від джерела викиду Приведены краткое описание Европейской системы прогноза радиационных последствий в режиме реального времени RODOS и расчетного кода MELCOR Accident Consequence Code System (MACCS), рассмотрена возможность применения этих кодов для оценки влияния радиационного облучения на население и окружающую среду в условиях тяжелой аварии на АЭС в режиме реального времени. Выполнен сравнительный анализ результатов расчетов, проведенных с использованием кодов RODOS, WinMACCS и HotSpot. В рамках исследования для рассмотрения выбраны следующие критерии: эффективная доза облучения, эквивалентные дозы облучения щитовидной железы и кожи, поверхностные концентрации радионуклидов I-131 и Cs-137 на расстояниях до 50 км от источника выброса